Synthesis and Characterization of Novel HPMC Phthalate Succinate Polymers for Pharmaceutical Applications - Babu, Nagella Raveendra; Awasthi, Rajendra; Ankola, Dhawal; Nagpal, Dheeraj (Indian Journal of Pharmaceutical Education and Research, 2025)
Aim: The current article aimed to synthesize new HPMC derivative polymers by esterification method. Background: 2 most common causes of drug candidate failures are a lack of effectiveness and PK/bioavailability issues. Various strategies have been employed to enhance the aqueous solubility of pharmaceuticals, with one significant technique being solid dispersion. In the last decade, most drug products launched using the solid dispersion technique have utilized HPMCAS polymer as a carrier due to its unique advantages. These products are protected by patents, creating a need for novel polymers to facilitate easier access to generics. Materials and Methods: HPMC, Phthalic anhydride, Succinic anhydride, Sodium acetate and Acetic acid were used for the synthesis of new polymer. Polymers with different ratios of phthalate anhydride and succinate anhydride were characterized using various spectroscopic techniques. The effect of the degree of modification on molecular characteristics was examined by FTIR, 1H and 13C nuclear magnetic resonance techniques. Further, novel polymer properties such as glass transition temperature and thermal stability were studied using thermogravimetric analysis and differential scanning calorimetry. The physical form of synthesized polymer was determined using X-ray diffraction analysis technique. For establishing pharmaceutical applications of the novel polymer, solubility and film forming nature were investigated. Results and Conclusion: The results confirmed that the synthesis of HPMC derivative is an esterification reaction where -OH in HPMC reacts with anhydride and results in esterification. NMR spectra confirmed successful synthesis of succinate and phthalate succinate derivatives of HPMC. All polymers, except HPMC phthalate succinate 73, displayed an amorphous structure. The novel polymer(s) appears to be rounded to elongated particles with a diameter less than 5 microns and is dense. Compared to the novel polymers synthesized, HPMCAS required more solvent to form a clear solution in the selected solvent system. Polymer films, except HPMC succinate, remained intact in 0.1N HCl (pH 1.2) and acetate buffer (pH 4.5). However, the films were dissolved in phosphate buffer (pH 6.8). The results indicate that the synthesized polymer can be used in enteric coated or gastrointestinal tract targeted drug delivery systems.
Keywords: Dissolution enhancement; Hydroxypropyl methylcellulose acetate succinate; Hydroxypropyl methylcellulose phthalate succinate; Polymer synthesis; Solid dispersion